2003
DOI: 10.1152/ajpheart.00988.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effects in subthreshold virtual electrode polarization

Abstract: Introduction of the virtual electrode polarization (VEP) theory suggested solutions to several century-old puzzles of heart electrophysiology including explanation of the mechanisms of stimulation and defibrillation. Bidomain theory predicts that VEPs should exist at any stimulus strength. Although the presence of VEPs for strong suprathreshold pulses has been well documented, their existence at subthreshold strengths during diastole remains controversial. We studied cardiac membrane polarization produced by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…We did not observe the classically described dogbone-shaped potential distributions; however, we measured tissue responses at steady state, 200 ms after the stimulus onset. Others (39) have reported that low stimulus strength induces an initial dogbone-shaped field that spreads out nonuniformly, such that it can no longer be easily detected after 10 ms.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe the classically described dogbone-shaped potential distributions; however, we measured tissue responses at steady state, 200 ms after the stimulus onset. Others (39) have reported that low stimulus strength induces an initial dogbone-shaped field that spreads out nonuniformly, such that it can no longer be easily detected after 10 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated biophysical theories have been developed that predict the distribution of the transmembrane and extracellular potentials inside the heart during electrical shocks. Major successes were the prediction of the dog-bone-shaped polarization in anisotropic myocardial tissue (5)(6)(7), the formation of quatrefoil reentry (8), and qualitative patterns of surface polarization during defibrillation shocks in the whole heart (9). However, recent optical imaging studies utilizing voltage-sensitive dyes have revealed several major discrepancies between theory and experiment that cannot readily be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, virtual electrodes predicted by the bidomain model have been demonstrated empirically over cardiac myocardium [60],[61]. Thus, the ability of a network of passive cable elements to generate VE, is well supported.…”
Section: Discussionmentioning
confidence: 83%